👤

Va rog ex c) mulțumesc !

Va Rog Ex C Mulțumesc class=

Răspuns :

Efektm

Răspuns:

[tex]y = -23\sqrt{2}[/tex]

Explicație pas cu pas:

c)

[tex]\frac{y-\sqrt{2} }{3} + \frac{y+\sqrt{2} }{2} = 4\sqrt{2} + y[/tex]

[tex]\frac{y-\sqrt{2} }{3} + \frac{y+\sqrt{2} }{2} - 4\sqrt{2} - y = 0[/tex]

[tex]\frac{2(y-\sqrt{2}) + 3(y+\sqrt{2}) - 6*4\sqrt{2} - 6y }{6} = 0[/tex]         (am adus la același numitor)

[tex]2y - 2\sqrt{2} + 3y + 3\sqrt{2} - 24\sqrt{2} - 6y = 0[/tex]

[tex]- y - 23\sqrt{2} = 0[/tex]

[tex]-y = 23\sqrt{2}[/tex]

[tex]y = -23\sqrt{2}[/tex]